2008
DOI: 10.1590/s1806-37132008001200006
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da concentração de alfa 1-antitripsina e da presença dos alelos S e Z em uma população de indivíduos sintomáticos respiratórios crônicos

Abstract: Objective: To determine the levels of alpha-1 antitrypsin (AAT) and the presence of S and Z alleles in patients with chronic respiratory symptoms. Methods: Patients with chronic cough and dyspnea were submitted to clinical evaluation, pulmonary function tests, high-resolution computed tomography, nephelometric determination of AAT and determination of S and Z alleles by polymerase chain reaction. Smoking and AAT levels were considered the dependent variables. Results: Of the 89 patients included in the study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…This enzyme is produced by neutrophils in response to some inflammatory stimuli and aims to destroy aggressive agents. However, since it is one of the few human enzymes capable of degrading elastic fibers, it can lead to the destruction of tissues, especially those of the alveolar walls [3, 4]. Nevertheless, AAT is considered important as it acts as an antagonist of neutrophilic enzymes and is responsible for 90% of all anti-protease activity in human serum; the remaining 10% is undertaken by α 2 -macroglobulin [1, 3, 5, 6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This enzyme is produced by neutrophils in response to some inflammatory stimuli and aims to destroy aggressive agents. However, since it is one of the few human enzymes capable of degrading elastic fibers, it can lead to the destruction of tissues, especially those of the alveolar walls [3, 4]. Nevertheless, AAT is considered important as it acts as an antagonist of neutrophilic enzymes and is responsible for 90% of all anti-protease activity in human serum; the remaining 10% is undertaken by α 2 -macroglobulin [1, 3, 5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…However, since it is one of the few human enzymes capable of degrading elastic fibers, it can lead to the destruction of tissues, especially those of the alveolar walls [3, 4]. Nevertheless, AAT is considered important as it acts as an antagonist of neutrophilic enzymes and is responsible for 90% of all anti-protease activity in human serum; the remaining 10% is undertaken by α 2 -macroglobulin [1, 3, 5, 6]. Serum levels of AAT can be elevated following acute or chronic inflammation, infections, presence of certain neoplasms, severe burns, or during pregnancy and contraceptive use [7].…”
Section: Introductionmentioning
confidence: 99%
“…Os neutrófilos, uma das principais células presentes na inflamação pulmonar, são responsáveis pela produção de serinas proteases, enzimas proteolíticas neutrofílicas que apresentam várias atividades, como a degradação de fibras elásticas no tecido pulmonar, sendo uma das poucas enzimas humanas capazes de realizar essa destruição 13 .…”
Section: Resultado E Discussãounclassified
“…In a recent study, Russo et al found that 2.8% of patients with COPD in Brazil had A1ATD, 2 which is an alarming finding considering the low frequency of this diagnosis in clinical practice and the small number of articles published on A1ATD in the Brazilian population. 2 , 15 Our country has a vast racial diversity, miscegenation and European immigration from countries where the frequency of alleles involved with A1ATD is high.…”
Section: Discussionmentioning
confidence: 99%